2021
DOI: 10.1007/s13394-021-00365-y
|View full text |Cite
|
Sign up to set email alerts
|

Students’ agency, creative reasoning, and collaboration in mathematical problem solving

Abstract: This paper aims to give detailed insights of interactional aspects of students’ agency, reasoning, and collaboration, in their attempt to solve a linear function problem together. Four student pairs from a Norwegian upper secondary school suggested and explained ideas, tested it out, and evaluated their solution methods. The student–student interactions were studied by characterizing students’ individual mathematical reasoning, collaborative processes, and exercised agency. In the analysis, two interaction pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Mathematical thinking is crucial in learning and teaching mathematics (Stacey, 2006). When students think mathematically, they actively engage in their mathematics learning, attempting to make sense of ideas and constructing connections among various facts, procedures, and concepts (Hwang & Ham, 2021;Hansen, 2022). Moreover, effective mathematics learning officially starts with thinking activities in the learning process.…”
Section: Student' Response To the Tasksmentioning
confidence: 99%
“…Mathematical thinking is crucial in learning and teaching mathematics (Stacey, 2006). When students think mathematically, they actively engage in their mathematics learning, attempting to make sense of ideas and constructing connections among various facts, procedures, and concepts (Hwang & Ham, 2021;Hansen, 2022). Moreover, effective mathematics learning officially starts with thinking activities in the learning process.…”
Section: Student' Response To the Tasksmentioning
confidence: 99%
“…However, researchers (i.e., Hansen, 2021;Öztürk et al 2020;Passolunghi et al, 2019) found that students' mathematics problem solving is influenced by affective factors. In fact, several emotional changes were captured in the study conducted by O'Dell (2018).…”
Section: What Are the Foci Of The Research On Problem Solving In Elem...mentioning
confidence: 99%
“…Despite the strong consensus among the mathematics education community on recognizing the development of students' mathematics problem solving ability as the main goal in the classroom, Lester and Cai (2016) noted that the consensus on effective instruction for developing students' problem solving ability is yet to be reached. Following this, Hansen (2021) urged the researchers to conduct more research on mathematics problem solving. Nonetheless, it is argued that the lack of accumulation of problem solving research is the main issue to be addressed for avoiding the recycling of flawed conjectured problem solving instructions in future research (English & Sriraman, 2010) Thus, it is warranted to conduct a review of the pastrelated studies for identifying the research gaps (Cason et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used by students and teachers to actively develop and comprehend mathematical ideas (Lam, 2012). Moreover, reasoning has the ability to improve students' understanding of mathematics and enhance the development of their creativity (Hansen, 2021). It is very important to develop students to participate in creative thinking activities (Nogerbek et al, 2022).…”
Section: Conceptual Frameworkmentioning
confidence: 99%